DETERMINAN KESIAPSIAGAAN BENCANA PADA MAHASISWA - Nopianto; Utami, Nurul; Fitria, Eliza (Jurnal Kesehatan, 2024)
The BNPB annual report shows 3,058 natural disaster events throughout 2021. The most appropriate stage of disaster management to reduce disaster risk is in the pre-disaster stage. Preliminary study of 6 students at STIKes Tengku Maharatu, it was found that the level of student knowledge related to disaster was low. This study used a quantitative method with a cross sectional design, conducted at STIKes Tengku Maharatu and carried out in July 2022. The population is 161 active students at STIKes Tengku Maharatu. The study used 115 samples taken using simple random sampling. Data analysis was carried out univariate and bivariate with chi square test. The results showed that the variables that were significantly related to disaster preparedness among students at STIKes Tengku Maharatu were knowledge (p=0.005), attitude (p=0.007). Meanwhile, the unrelated variable is the force (p=0.394). Based on the results of the study, it can be concluded that the knowledge and attitude variables are related to disaster preparedness, the force variable is not related to disaster preparedness for students at STIKes Tengku Maharatu.